Debt Covenant Restriction, Financial Misreporting, and Auditor Monitoring* - Pittman, Jeffrey; Zhao, Yuping (Contemporary Accounting Research, 2020)
ABSTRACT Theory suggests that financial report‐based debt covenants engender incentives for the manager to relax covenant constraints through accounting choices in order to avoid costly covenant violations. Prior studies directly testing this hypothesis in the context of financial misreporting fail to find consistent evidence. Using a more refined measure of debt covenant restriction, we find that debt covenant restriction is positively associated with the probability of financial statement misstatements. This positive association is driven by performance covenants rather than capital covenants and is more consistent with the manager striving to avoid a “false‐positive” violation than to delay the violation. Our results also imply that managers resort to both income‐increasing and non–income‐increasing misreporting to relieve covenant constraints and rely more on the latter when faced with greater earnings management constraints. Additionally, the auditor charges higher audit fees to firms with more binding covenants even outside the violation state, and audit fees increase with constraints relative to both performance and capital covenants, reflecting greater financial reporting risk and bankruptcy risk, respectively. Within capital covenants, we find some evidence of even higher audit fees for tighter intangible‐inclusive versus intangible‐exclusive capital covenants. Lastly, our evidence suggests that the positive association between covenant constraints and misreporting is attenuated when the auditor has more experience with debt covenants, has greater bargaining power over the client, or faces greater litigation risk.